Cytokinetic abscission requires actin-dependent microtubule severing - Tamara Advedissian; Stéphane Frémont; Arnaud Echard (Nature Communications, 2024)
Abstract Cell division is completed by the abscission of the intercellular bridge connecting the daughter cells. Abscission requires the polymerization of an ESCRT-III cone close to the midbody to both recruit the microtubule severing enzyme spastin and scission the plasma membrane. Here, we found that the microtubule and the membrane cuts are two separate events that are regulated differently. Using HeLa cells, we uncovered that the F-actin disassembling protein Cofilin-1 controls the disappearance of a transient pool of branched F-actin which is precisely assembled at the tip of the ESCRT-III cone shortly before the microtubule cut. Functionally, Cofilin-1 and Arp2/3-mediated branched F-actin favor abscission by promoting local severing of the microtubules but do not participate later in the membrane scission event. Mechanistically, we propose that branched F-actin functions as a physical barrier that limits ESCRT-III cone elongation and thereby favors stable spastin recruitment. Our work thus reveals that F-actin controls the timely and local disassembly of microtubules required for cytokinetic abscission.